Analis Strategi Pemasaran Pada Produk Manhole Menggunakan Metode SWOT Dan AHP Di PT XYZ - Rickhi Hidayat; Yohanes Anton Nugroho (Lembaga Pengembangan Kinerja Dosen, 2023)
XYZ is a company engaged in the metal casting and machining industry, playing a role as a company that produces products and markets its products in various regions. The formulation of marketing strategy analysis needs to be carried out in this research so that it can compete more with other competitors. While SWOT is an analytical method that is widely used to determine strategic factors, which are based on strengths, weaknesses, opportunities and threats, owned by a company. But in fact the SWOT method raises many alternative strategies, making it less efficient in determining the marketing strategy decisions to be used. Therefore, the Analytical Hierarchy Process (AHP) method is needed, with this method you can choose the best alternative based on information on the most preferred alternative. Because this method can focus on a problem to be solved and can be framed in a more organized frame of mind, so that decision making can be more effective on existing problems, namely Strength Opportunity (SO), Weakness Opportunity (WO), Strength Threats (ST), Weakness Threats (WT). The determination of the AHP method produces Weakness Threats (WT) with the highest weight of 5.61 as the strategy chosen to be applied to PT. XYZ, namely, always continue to innovate in utilizing technology properly, especially in marketing management so that the product promotion process can be maximized, then by continuing to be active in promoting so as not to lose competitiveness with the popularity of other competitors.